An appraisal of scope for women-led entrepreneurship in dairying - Ponnusamy, Kuppusamy; Sabikhi, Latha; Meena, G S (Indian Journal of Dairy Science, 2020)
This study assessed the scope of women-led entrepreneurship in dairying and allied enterprises by using a structured interview schedule. The sample size consisted of 162 respondents who were working as field extension functionaries, academicians and agro-based entrepreneurs across the country. The study revealed that the most of respondents belonged to middle age group (36-50 years) followed by young age group (upto 35 years). Half of respondents had working experience of 11-20 years. Commercial dairy farming (60%) under production domain, preparation of value added milk and milk products (59.9%) under processing domain and establishment of milk parlour in urban areas (77.16%) under marketing domain were perceived by respondents as potential areas for entrepreneurship in dairying. The respondents considered low level of education/knowledge (58.6%), lack of family and financial support (56.8%) and household responsibility (30.2%) as hurdles for participation of women in entrepreneurship. They opined that better remunerative prices (30.9%), government support (28.4%) and providing education and need-based training (25.3%) could motivate women to take up entrepreneurship. They suggested that providing education and training (47.5%), awareness through exposure visits and motivation camps (42.6%) and development of market facilities/linkages (24.1%) would be effective strategies to motivate youth and women in agro-based entrepreneurship. Support systems like creating awareness among women about available opportunities (35.2%) and formation of self help groups (29.6%) along with providing subsidies and incentives (45.7%) would strengthen the hands of women for venturing into agri-business. The study concluded that dairying has very large scope (54.9%) for women-led entrepreneurship provided with proper hand holding support, training and motivation.